Labour-related Causes Controlling the Efficiency of Road Construction Operations in Sri Lanka: Engineers’ Standpoint - Manoharan, Kesavan; Dissanayake, Pujitha; Pathirana, Chintha; Deegahawature, Dharsana; Silva, Renuka (Advances in Technology, 2022)
The efficiency of workforce operations has a significant impact on how profitable a construction firm is. Studies from the past demonstrate that a variety of labour-related concerns have been affecting the construction sector in Sri Lanka and other developing countries, which has a negative impact on the efficiency of construction activities. Construction engineers are crucial resources who can play a key role in the development of decisions and regulations pertaining to construction labourers. This study intends to examine the influence of labour-related causes on the efficiency of construction operations in Sri Lankan road construction projects from the perspective of construction engineers. The significant labour-related causes were identified by a comprehensive scholarly review. Then, a questionnaire survey was conducted among 31 road construction contractors in Sri Lanka. The impact level of each cause was calculated using the Relative Importance Index (RII) method. A total of 26 causes were found to be critical, where labour skill shortage, labour discipline, labourers’ poor ability of reading, understanding, speaking and writing, labourers’ lack of thinking abilities and their communication problems were the top five ranking causes in the list. The validity and reliability of the study findings were established using statistical testing. The activities required in the construction site management processes were also evaluated in relation to the key variables identified through a number of industry consultative sessions. These consultative outcomes further confirmed the validity of the study results. The study findings will significantly aid in modernising current industry practices to boost output and efficiency. Even though the study findings are applicable and limited to the Sri Lankan road construction sector, some of those may still be considered in other developing sectors/countries.